The use of science and culture magazines of Philological Sciences Reading Room collection (Confluenţe Bibliologice, 2012)
The article reﬂects the development, requirement and use of science journals collection and philological culture in Philology Sciences Reading Room. Some aspects are analysed with regard to the importance of traditional serial publications in the educational process and research for students and teachers, the results of polls conducted is talking about.
Keywords: scientific journals; periodicals; collection of USARB SL